PREVALENCE OF METABOLIC SYNDROME AMONG BAMILEKE ETHNIC WOMEN YAOUNDE, CAMEROON - DAMARIS ENYEGUE MANDOB; GILLES INES DONGMO FOMEKONG; JUDITH LAURE NGONDI (International Journal of Pharma and Bio Sciences, 2013)
Metabolic Syndrome (MetS) is the cluster of several cardiovascular risks. A study population of one hundred and thirty four women in Yaoundé Cameroon aged between (20-60 years) were scrutinized using Adult Treatment Panel-III definition. The mean age, body mass index, waist circumference, systolic blood pressure, diastolic blood pressure, triglyceride and fasting blood glucose levels were significantly higher in women with MetS and the mean of HDL-cholesterol was lower (p<0.001). The prevalence of MetS was 44.77% and was decreasing with aging; the younger adult women were more affected. Low HDL-cholesterol (79.85%) and high abdominal (64.17%) obesity level are respectively the most frequent characteristics in comparison to other metabolic components. According to our results, 35.07%, 9.70% and 0.00% had three, four and five MetS components correspondingly. MetS prevalence in these women is high; some factors have been pointed out in this study. Women should be scrutinised in other ethnics group of Cameroon.